Wood Industry Past, Present and Future Outlook - Du, Guanben; Zhou, Xiaojian (IntechOpen, 2023)
Wood has been widely used in many aspects of our daily life for thousands of years. It is used in every possible unit size from macro to micro and even nanoscale. It can also be combined with various polymer systems to obtain composites with excellent performance. The aim of this book is to present traditional, current and future advanced functional wooden composites from different countries. The most recent research into novel advanced techniques for "super wood" products and their various functionalities in high value-added sectors is also covered.